Pembangunan pelancongan Kuala Kedah untuk "semua": Kriteria dan tanda aras kelestarian untuk pertimbangan - Ahmad, Mohamad Zaki; Ibrahim, Johan Afendi; Abdul Razak, Norhanim (2012)
Kuala Kedah, a small town popularly known as a fisherman "village" in Muara Sungai Kedah, really has few great attractions particularly historical relics and its interestingly unique natural landscapes.With abundance of heritage and natural touristic resources together with good infrastructural facilities, Kuala Kedah surely does have a great potential to be developed as a new tourism destination.Hence, development of Kuala Kedah as a tourism destination potentially can contribute great positive impacts and benefits towards the enhancement of its local community's socioekonomic standard.Realizing that most tourist main attractions are dependent on non-renewable natural and heritage resources, preservation and corservation efforts of those resources should be properly and continuously carried out.In this context, the concept of sustainable development is one of the best alternatives to be practiced and adapted in any tourism-related development in Kuala Kedah.Therefore, to assist various stakeholders to come up with a 'sound' tourism development that has great potential in generating positive "outputs" to "all", this seminar paper is proposing "critiria and indicators of sustainability" for consideration in Kuala Kedah's tourism development process.